Antioxidant Capacity, Phytochemical Analysis and Identification of Active Compounds in Anchomanes difformis - Alabi, Toyin D.; Brooks, Nicole Lisa; Oguntibeju, Oluwafemi Omoniyi (Natural Products Journal, The, 2020)
Background: Anchomanes difformis (ENGL: Blume) is a specie of flowering plants in the family Araceae. Anchomanes difformis is commonly reported for ameliorating hyperglycemia, inflammation, ulcer, malaria, and inhibiting microbial growth. Objective: This study evaluated total yields of phytochemicals present, measured antioxidant capacities and identified bioactive compounds in the leaves and rhizome extracts of A. difformis using solvents of different polarity (ethyl acetate, ethanol and water). Methods: Total polyphenolic, flavonoid content and alkaloids were measured, ORAC, TEAC and FRAP were performed as antioxidant capacity indices, and identification of bioactive compounds was done using UPLC-MS and HPLC. Results: All extracts contained polyphenols, flavonols, flavanols, and alkaloids in varying concentrations. All extracts exhibited antioxidant properties. However, aqueous leaves extract had the highest antioxidant properties and polyphenols with significance (p<0.05). Thirty-four compounds were identified altogether in the leaves and rhizome. Conclusion: A. difformis leaves and rhizome are potential sources of natural antioxidants and can serve as potential therapeutic agents against diseases linked with oxidative stress. Presence of health-promoting compounds indicates possible ameliorative potentials of A. difformis.
Keywords: phytochemicals